Fusarium Spp. In Tropical Asia: Their Taxonomy, Pathogenic, Genetic And Molecular Aspects - Salleh, Baharuddin (2004)

(untitled)
Fusarium is one of the most interesting genera of pathogenic And toxigenic fungi widely distributed all over the world, including Southeast Asia.